Estudio de la variabilidad genética del DRD4 y del DAT1 en individuos habitantes de la Ciudad de México - Gabriela Ariadna Martínez-Levy (Salud Mental, 2013)
Family, twin and adoption studies suggest that genetics plays an im- portant role in the etiology of many psychiatric disorders. It has been proposed that the dopaminergic brain system could be affected in schizophrenia, substance abuse and attention deficit hyperactivity dis- order. The most studied genes are two VNTR polymorphic systems; one located in the exon 3 of the dopamine D4 receptor (DRD4) gene, and the other in the 3` untranslated region of the dopamine trans- porter (DAT1 or SCLA6A3) gene. It has been reported that allele fre- quencies of these polymorphisms varied between populations and this could affect the results in the association studies. Due to the previous findings, the objective of the present study was to determine the allele frequencies of DRD4 and DAT1 in an epidemiological sample of the adolescent population of México City. We found that the frequencies presented in our study were in between those reported for Caucasians and those reported for the American Indigenous population, this result are consistent with Euro-Indigenous inbreeding that has occurred in Mexico. Moreover, the results presented in the present study could explain the lack of consistency in the association analysis and make necessary to develop these investigations in our population.